Silicon nanowires enhanced proliferation and neuronal differentiation of neural stem cell with vertically surface microenvironment. Issue 13 (2nd September 2017) - Yan, Qiuting; Fang, Lipao; Wei, Jiyu; Xiao, Guipeng; Lv, Meihong; Ma, Quanhong; Liu, Chunfeng; Wang, Wang
Abstract: Owing to its biocompatibility, noncytotoxicity, biodegradability and three-dimensional structure, vertically silicon nanowires (SiNWs) arrays are a promising scaffold material for tissue engineering, regenerative medicine and relevant medical applications. Recently, its osteogenic differentiation effects, reorganization of cytoskeleton and regulation of the fate on stem cells have been demonstrated. However, it still remains unknown whether SiNWs arrays could affect the proliferation and neuronal differentiation of neural stem cells (NSCs) or not. In the present study, we have employed vertically aligned SiNWs arrays as culture systems for NSCs and proved that the scaffold material could promote the proliferation and neuronal differentiation of NSCs while maintaining excellent cell viability and stemness. Immunofluorescence imaging analysis, Western blot and RT-PCR results reveal that NSCs proliferation and neuronal differentiation efficiency on SiNWs arrays are significant greater than that on silicon wafers. These results implicate SiNWs arrays could offer a powerful platform for NSCs research and NSCs-based therapy in the field of neural tissue engineering.